2020
DOI: 10.1172/jci.insight.137788
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic receptor activation on donor cells ameliorates acute GvHD

Abstract: warmer, thermoneutral temperature (TT). Housing mice at TT substantially reduces norepinephrine and β-AR signaling on immune cells (22). Treatment of allo-HCT mice housed at ST with the pan-beta blocker propranolol increased aGvHD severity, indicating that β-AR signaling is protective against aGvHD (22). Furthermore, we demonstrated that blockade of recipient β2-ARs enhanced the GvT effect by modulating antigen presenting cells (23). It was critical to continue to define the role of T cell β2-AR signaling, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
1
16
1
Order By: Relevance
“…Recently, one promising approach in endogenous MDSC generation was achieved with the help of β 2 -AR agonists in a murine model of GVHD ( 52 ). Treatment with bambuterol – a prodrug of the selective β 2 -agonist terbutaline – significantly increased the number of MDSCs and Tregs while effector T cells were reduced and GVHD was ameliorated ( 52 ). All other mechanisms of action were excluded, and the central role of β 2 -AR was confirmed ( 52 ).…”
Section: Pharmacological Approaches To Modulate Mdscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, one promising approach in endogenous MDSC generation was achieved with the help of β 2 -AR agonists in a murine model of GVHD ( 52 ). Treatment with bambuterol – a prodrug of the selective β 2 -agonist terbutaline – significantly increased the number of MDSCs and Tregs while effector T cells were reduced and GVHD was ameliorated ( 52 ). All other mechanisms of action were excluded, and the central role of β 2 -AR was confirmed ( 52 ).…”
Section: Pharmacological Approaches To Modulate Mdscsmentioning
confidence: 99%
“…Treatment with bambuterol – a prodrug of the selective β 2 -agonist terbutaline – significantly increased the number of MDSCs and Tregs while effector T cells were reduced and GVHD was ameliorated ( 52 ). All other mechanisms of action were excluded, and the central role of β 2 -AR was confirmed ( 52 ). Accordingly, in vitro cultivation of MDSCs is also increased by terbutaline ( 52 ).…”
Section: Pharmacological Approaches To Modulate Mdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Mohammadpour et al extended these findings using different models of allogeneic and xenogeneic models of HSCT. They found that adoptive transfer of allogeneic, β2-AR deficient (β2-AR −/− ) CD4 + T cells (with BM) into lethally irradiated recipients induced more severe aGVHD than did engraftment with wild type (WT) allogeneic T cells [139]. The exacerbation of disease in mice engrafted with β2-AR −/− CD4 + T cells was associated with increased numbers Th1 effector cells whereas transfer of WT T cells resulted in increases in Tregs, Th2 cells and myeloid derived suppressor cells [139].…”
Section: Inflammationmentioning
confidence: 99%
“… 30 , 31 , 32 , 33 , 34 The strong, naturally occurring immunosuppressive potential of β‐AR signalling is consistent with our observations that adrenergic stress or addition of β‐AR agonists can suppress graft versus host disease (GVHD) following allogeneic bone marrow transplantation (BMT). 34 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%